Varför kan man tvätta med tvättnötter (Sapindus mukorossi)? : en litteraturstudie om de aktiva ämnena i tvättnötter och hur de fungerar vid tvätt av kläder - Fredriksson, Magdalena (SLU/Horticulture (until 121231), 2010)

(untitled)
Soapnuts have been used as a cleaning detergent and medicine since ancient times in different parts of Asia. Today soapnuts are sold as an environmentally friendly alternative to common washing detergents. The aim of this literary study is to give an answer to what it is in the soapnuts that makes them work as a washing detergent. The active component belongs to a group of components called saponins which are secondary metabolites with the purpose to protect the tree from pathogen attacks. Saponins are widely spread in the vegetable kingdom and some of the families and species are so rich in saponins that their names are influenced by this, for example Sapnindaceae and Sapindus which are mentioned in the beginning of this literary study. Soapnuts can be used as a whole fruit or only the pericarp but also as a powder or as a liquid detergent after processing the shells. Just like washing detergents and soap the saponins in soapnuts has a polar (hydrophilic) part and a non-polar (lipophilic) part which means that it has the same possibility to work as a cleaning detergent. The lipophilic part consists of an aglycone (sapogenin) and the hydrophilic part consists of a branched or linear chain made of different kinds of monosaccharide.